2012
DOI: 10.1007/s11019-012-9449-x
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of undesirable truths

Abstract: The right not to know is often defended on the basis of the principle of respect for personal autonomy. If I choose not to acquire personal information that impacts on my future prospects, such a choice should be respected, because I should be able to decide whether to access information about myself and how to use it. But, according to the incoherence objection to the right not to know in the context of genetic testing, the choice not to acquire genetic information undermines the capacity for autonomous decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Some researchers have suggested that individuals have a right not to know in the context of genetic predictive testing, and various international conventions have recognized this right (Wehling, 2015). Others have argued that ignorance undermines self-governance (see Harris & Keywood, 2001, and discussions in Bortolotti, 2012).…”
Section: When Is Deliberate Ignorance a Good Thing?mentioning
confidence: 99%
“…Some researchers have suggested that individuals have a right not to know in the context of genetic predictive testing, and various international conventions have recognized this right (Wehling, 2015). Others have argued that ignorance undermines self-governance (see Harris & Keywood, 2001, and discussions in Bortolotti, 2012).…”
Section: When Is Deliberate Ignorance a Good Thing?mentioning
confidence: 99%
“…It is common to maintain that my doctor wrongs me here (Andorno , Bortolotti , Bortolotti and Widdows , Husted , Wilson ). Indeed, this view is codified in several international agreements on human rights .…”
Section: An Analogy In Medical Ethicsmentioning
confidence: 99%
“…However, at one point in their paper (when they try to explain why suicide is consistent with their idea of autonomy) Harris and Keywood (2001: 420) themselves admit that "Autonomy is not simply the exercise of choice but of control -literally self-government". More precisely one could say, following Bortolotti (2013), that autonomy is about "self-authorship" of one's life (within the social relations one lives in as well as within the given external restrictions of self-authorship) rather than about an obligation to be perfectly informed. Seen from this perpective, a person who feels compelled to acquire ever more knowledge and to continously make informed choices can swiftly lose control of her life and thus appears to be far less autonomous than another person who follows her own life plans and decides on her own how much and which genetic information she wants to have.…”
Section: Discursive Contestations: Ignorance and Autonomymentioning
confidence: 99%